Accredited Endoscopy Unit Program of Korea: Overview and Qualification - Jung-Wook Kim; Yu Kyung Cho; Jin-Oh Kim; Jae-Young Jang (Clinical Endoscopy, 2019)
The Korean Society of Gastrointestinal Endoscopy introduced the Accredited Endoscopy Unit Program to enhance endoscopy unit quality through systematic quality management in 2012. It was gradually expanded from training hospitals to institutions with 100+ beds, and the criteria for certification were applied according to the actual conditions of each institution. On the basis of the continuous communication with the institutions and feedback, the Accredited Endoscopy Unit Program certification criteria were revised in 2019 and introduced as follows: (1) the qualification criteria for endoscopy doctors and nurses; (2) facilities and equipment; (3) endoscopic examination process; (4) performance; (5) disinfection and infection control; and (6) endoscopic sedation. The assessment items consist of essential and recommended items. All essential items must be met for accreditation to be awarded. The assessment criteria for each evaluation area were revised as follows: (1) upgrading assessment criteria; (2) qualification of endoscopists and reinforcement of quality control education; (3) detailed standards for safety, disinfection, endoscopic sedation, and management instructions; and (4) presentation of new performance measurement of endoscopy and colonoscopy.